Low incidence of subsequent bacteraemia or fungaemia after removal of a colonized intravascular catheter tip. (May 2018) - Buetti, N.; Lo Priore, E.; Atkinson, A.; Kronenberg, A.; Marschall, J.; ,
Abstract: Objectives: We determined the frequency of subsequent bloodstream infection more than 2 days after removal of a catheter with positive tip cultures. Methods: We conducted a nationwide, observational study on intravascular catheter (IVC) tip cultures in Switzerland from 2008 to 2015 using data from the Swiss Antibiotic Resistance Surveillance System (ANRESIS). An IVC tip culture was included in the analysis if at least one microorganism could be cultivated from it. We excluded all data from patients with concurrent bacteraemia with the same microorganism identified 7 days before to 2 days after IVC removal. Subsequent bloodstream infection was defined as isolating (from blood cultures performed more than 2 days up to 7 days after catheter removal) the same microorganism as the one recovered from the IVC. Data on antibiotic therapy were not available in this surveillance study. Results: Over the 8-year period, 15 033 positive IVC tip cultures were identified. Our study population comprised 12 513 episodes of positive IVC tip cultures without concurrent bacteraemia. The frequency of sBSI was 1.8% ( n = 219). Subsequent bloodstream infections were more frequently detected after identification of C. albicans (10/113, 8.8%), S. marcescens (9/169, 5.3%), and S. aureus (30/623, 4.8%) on a catheter tip. Conclusions: A very low incidence of subsequent bloodstream infection was observed if a microorganism was identified on a removed IVC tip without concurrent bacteraemia. The risk of subsequent bloodstream infection increased if C. albicans, S. aureus, or S. marcescens were identified in this context.